The Civil War in Greece and Relations with Albania According to the Communist Press During 1948 – 1949 (European Journal of Multidisciplinary Studies, 2016)
During 1948-1949 relations with Greece were very tense in the postwar period of World War II. The positioning of the two countries in two different camps, respectively Albania in the Socialist Camp and Greece in the Western Camp, lead to even more severe relations between these two countries. The Greek Civil War, fought between two Greek groups, the democratic and the communist one, also involved Albania in the propaganda as supporting the right wing of the Communist Greek. Such a propaganda was retaliated by the Greeks in the Albanian territory, for a few days in the Albanian land. The Albanian press of that time was very much involved by mainly giving information of the propaganda oriented towards Moscow, rather than about the immediate risk the country was directly facing. In many cases, the war and the threat it imposed was transformed and far away from reality. The press of that time mostly transmitted what Stalinist Moscow directed, rather than the truth. It was Stalinist Moscow the place which Enver Hoxha held as the orienting point, especially after breaking relations a few months ago with the Communist Yugoslavian state. The Communist press of that time was more preoccupied about the advancement of the Greek communist forces, rather than the threat the democratic wing imposed by approaching the Albanian border. This showed that the Albanian State was displaying itself since the first steps as being indoctrinated and related to the ideology and not to the threat imposed to the Albanian nation. The communist press of that time varied in numbers and kinds, displayed in every newspaper or magazine the success of the Greek communism. Such a problem is also presented in the British parliament as an unfair action from the Albanian state